The role of international organizations in implementing the rules for the protection of human remains - Mohammed, Sara; Salam, Rana (Journal of Legal Sciences, 2022)
Our research will highlight the most prominent measures taken by international organizations to address the most prominent effects of armed conflict and genocide that result in large numbers of corpses and the mechanisms for searching human remains and identifying identification.